Process Control Ladder Logic Trouble Shooting Techniques Fundamentals - Kamel, Khaled; Kamel, Eman (IRO Journal on Sustainable Wireless Systems, 2019)
Programmable Logic Controller (PLC) based process control automation projects are a multiphase task requiring months of planning, specification documentation, design, implementation, debugging, and final commissioning. Debugging real time process control implementation is a three-phase process; logic simulation debugging, field static checkout, and in plant final testing and tuning. This paper briefly discusses the fundamental techniques used in the first two stages of implemented ladder logic debugging [5, 6]. A wastewater treatment facility for the processing of high flow storm rainwater using the Allen Bradley (AB) SLC 500 PLC is used to illustrate the concepts discussed. The rainwater is channeled to two large wet wells, the east wet well and the west wet well. The water is pumped to the river from the two connected wells at constant rate using a predefined process sequence control. Pumping station with multi motors deriving constant speed immersed pumps are used to regulate the discharge water flow and the level in the two wells. Only two pumps are assumed here; one in the east wet well and the other in the west wet well. The motors provide an input discrete signal indicating if the motor is running or not. The motors can also start by activating the Push Button located on the local panel if the AUTO/MAN switch is in Manual. Three float switches are used to provide an accurate indication of the water level at three prespecified critical east / west wet well locations. The Low-Level Float switch triggers the stopping of the running pump. The High-level Float switch triggers the starting of the scheduled pump. If the scheduled pump fails to start within more than 5 seconds, a backup pump is selected and started (not shown in this paper). An alarm must be issued in order to alert the operator of any motor failure. The Very High-level float switch triggers the starting of both pumps. If either of the two pumps fails to start the corresponding alarm is activated by the control. Pumps are scheduled to run according to an operator pre-defined calendar. This input is expected in hours of accumulated total pump run time. The two pumps must alternate while the water level is below the Very High Level and above the Low Level. Cascaded timers are not altered during the time when the two pumps are running. This paper shows the static and simulation debugging an abbreviated version of the typical original system used in wastewater facilities.